Answer :
Answer:
Step-by-step explanation:
2x+5x+3=0
7x+3=0
-3 -3
=0 =-3
7x=-3
-3/7=-0.42857142857
x=-0.42857142857
I think it is right
Answer:
The answer is actually [tex]x = \frac{-5+\sqrt{13} }{2}[/tex] or [tex]x = \frac{-5 -\sqrt{13} }{\ {2} }[/tex]
Step-by-step explanation:
We have the given equation:
[tex]x^{2} + 5x + 3=0[/tex]
- We have to use the quadratic formula in order to solve.
[tex]x = \frac{-b +or-\sqrt{b^{2}- 4ac } }{2a}[/tex]
+ or - in this formula stands for the symbol ±
- Given this formula:
[tex]x^2 + 5x + 3 = 0[/tex]
a = 1
b = 5
c = 3
- Plug it in:
[tex]x = \frac{-5+or-\sqrt{5^{2}-4(1)(3) } }{2(1)} \\\\x = \frac{-5+or-\sqrt{25-12} }{2} \\[/tex]
Solution:
[tex]x = \frac{-5+or-\sqrt{13} }{2}[/tex]
This is as far as it can be simplified.